Ribosome biogenesis-related gene signature predicts prognosis and immune landscape in glioma and identifies UTP20 as a therapeutic target - Li, Yadan; Tang, Xiaolong; Zhao, Wenhui; Si, Xiuwen; Cui, Yanfang; Dong, Yanbin; Liu, Yongshuo (Frontiers in Immunology, 2025)
BackgroundGlioma, the most prevalent primary brain tumor, exhibits dysregulated ribosome biogenesis closely linked to malignant behavior. However, the role of ribosome biogenesis in glioma and prognosis remains incompletely understood. This study aimed to construct a molecular signature based on ribosome biogenesis-related genes to predict patient survival and therapeutic response in glioma.MethodsUtilizing The Cancer Genome Atlas (TCGA) glioma cohort data, we constructed a ribosome biogenesis-related genes (RBRGs) signature using LASSO regression and multivariate Cox analyses, and subsequently validating its prognostic value in independent cohorts. We systematically evaluated the signature’s associations with clinicopathological features, tumor immunity, genomic instability, tumor stemness, and therapeutic sensitivity. The oncogenic role of the key gene UTP20 was experimentally validated in U87 and U251 glioma cell lines through MTS, colony formation, and transwell assays.ResultsWe established a four-gene RBRGs signature (NOP10, UTP20, SHQ1, and PIH1D2). Elevated RBRGs score significantly correlated with shortened overall survival and adverse clinical characteristics, including advanced age, high WHO grade, IDH wild-type status, and absence of 1p/19q codeletion. A nomogram incorporating the RBRGs score demonstrated excellent predictive performance (C-index = 0.841). RBRGs-associated genes were enriched in immune regulatory pathways. The high-risk group exhibited increased infiltration of immunosuppressive cells (macrophages, myeloid-derived suppressor cells [MDSCs], and cancer-associated fibroblasts [CAFs]), upregulation of immunosuppressive checkpoints, and resistance to immunotherapy. Furthermore, the RBRGs signature correlated with genomic alterations, heterogeneity, tumor stemness, and therapeutic sensitivity. Crucially, UTP20 knockdown significantly suppressed glioma cell proliferation and invasion in vitro.ConclusionThe RBRGs signature was successfully developed and validated as an independent prognostic biomarker and predictor of therapeutic response in glioma, highlighting its extensive association with tumor heterogeneity. Furthermore, this study identified UTP20 as a key oncogenic driver that facilitates glioma progression.